Dosimetric study of prostate brachytherapy, using Monte Carlo simulations and voxel phantoms. (September 2016) - Furtado, M.; Teles, P.; Laporte, C.; Khalfallah, N.; Broggio, D.; Costa, D.; Vaz, P.
Abstract : Introduction: Prostate brachytherapy is a radiotherapy technique whereby a set of sealed radioactive seeds are inserted in the prostate. In clinical practice, the absorbed dose in the prostate is determined using specific software. In this study, Monte Carlo (MC) simulations in a segmented voxel phantom of a real patient are used to determine the absorbed dose and the DVH in the prostate in comparison with those obtained from a conventional treatment planning procedure. The advantages of using this new method to determine absorbed dose over conventional treatment planning are discussed. Purpose: To estimate the absorbed dose and the DVH in the prostate and surrounding organs, using MC simulations and a voxel phantom segmented from CT images in comparison with values obtained from treatment planning software. Materials and methods: CT images of a patient submitted to low-dose rate brachytherapy (LDR) using Iodine-125 seeds were used to produce a voxel phantom. The MC simulations were performed with MCNPX software. The clinical absorbed dose and DVH were determined using the software Interplant®. Results: The voxel phantom was successfully created and defined to detail. The seeds' disposition used in the treatment planning was also recreated. The doses on the prostate as well as surrounding organs were calculated and compared with those registered in the treatment planning procedure. Conclusion: MC simulations in a segmented voxel phantom can be used as an alternative method for prostate brachytherapy treatment planning. This method has advantages over the ones used in clinical practice. These advantages include accounting for several parameters not fully considered during conventional treatment planning such as the prostate swelling, the use of real tissue parameters, post-implantation displacement of the seeds. The quantification of these parameters is provided and discussed in detail.